1-Hexanol as a sustainable biofuel in DI diesel engines and its effect on combustion and emissions under the influence of injection timing and exhaust gas recirculation (EGR). (25th February 2017) - De Poures, Melvin Victor; Sathiyagnanam, A.P.; Rana, D.; Rajesh Kumar, B.; Saravanan, S.
Highlights: 1-Hexanol was blended up to 30% by vol. with diesel in a diesel engine. Injection timings (21–25°CA bTDC) and EGR rates (10–30%) were used. Blend injected at 25°CA bTDC under 30% EGR was found to be favorable. Smoke density reduced by 35.9% with a slight penalty of ≈3% in NOx emissions. HC emissions remained higher and CO emissions decreased favorably. Abstract: 1-Hexanol is a high-carbon bio-alcohol with higher cetane number and higher energy density than the popularly researched 1-butanol that makes it an attractive fuel for diesel engines. Studies are rapidly emerging on high-yield bio-synthesis of 1-hexanol from glucose and ligno-cellulosic biomass feedstock using engineered micro-organisms like E. coli and Clostridium species. Despite its favorable properties and promising prospects for production in bio-refineries, 1-hexanol has been barely investigated in engines. This study utilized three blends of 1-hexanol viz ., HEX10, HEX20 and HEX30 obtained by mixing 10, 20 and 30% by vol. as blend component with diesel respectively. Engine tests were carried out at all loads to study the effects of 1-hexanol addition on combustion and emission characteristics of a direct injection diesel engine. Results indicated that addition of 1-hexanol to fossil diesel resulted in longer ignition delays with enhanced premixed combustion phase characterized by higher peaks of pressures and heat release rates (HRR) at the engines standard injection timing without exhaust gas recirculation (EGR). NOx emissions increased at high loads while smoke density reduced at all loads with increasing 1-hexanol content in the blends. Later tests were extended to investigate the effects of injection timing (21°, 23° and 25° CA bTDC) and EGR rates (10, 20 and 30%) on engine characteristics for all blends at high engine loads. HEX30 injected at 25°CA bTDC under 30% EGR presented the longest ignition delay with ≈2% increase in peak pressure and peak HRRs when compared to baseline diesel operation. HEX30 at similar conditions was also beneficial in terms of reduced smoke density by 35.9% with a slight penalty in NOx emissions by ≈3%. Biomass-derived 1-hexanol could be a promising and viable biofuel for existing diesel engines with some modifications.